2014
DOI: 10.5664/jcsm.3370
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gender on Timeliness of Narcolepsy Diagnosis

Abstract: the Yale Center of Sleep Medicine. All patients completed polysomnography (PSG) and multiple sleep latency test (MSLT), and a structured interview by an independent sleep specialist. Patients were administered a standardized 8-page questionnaire within 4 weeks of their narcolepsy diagnosis. Sixteen patients did not complete the questionnaire or had missing data, and were excluded. The study was approved by the Yale Institutional Review Board. QuestionnaireThe standardized questionnaire, in addition to other sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 51 publications
2
34
3
3
Order By: Relevance
“…In two separate studies from Europe and USA, women had a longer diagnostic delay than men [46,47]. This difference between men and women was not seen in the present study but, of note, the diagnostic delay for both genders was years shorter than in the literature.…”
Section: Discussioncontrasting
confidence: 83%
“…In two separate studies from Europe and USA, women had a longer diagnostic delay than men [46,47]. This difference between men and women was not seen in the present study but, of note, the diagnostic delay for both genders was years shorter than in the literature.…”
Section: Discussioncontrasting
confidence: 83%
“…33 In addition, gender seems to affect the interval between the symptom onset and diagnosis. Won et al 34 demonstrated that men are diagnosed on average 12 years earlier than women. The authors suggested that a possible factor involved in this delayed diagnosis is that women may be less forthcoming about their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil ini berbeda dengan hasil penelitian yang menyebutkan bahwa kondisi narkolepsi tidak berbeda antar jenis kelamin, hanya saja sering terjadi keterlambatan diagnosis pada perempuan (Won, et al, 2014).…”
Section: Masalah Tidur Berdasarkan Karakteristikunclassified